THE ROLE OF ELECTRONIC WORD OF MOUTH (E-WOM) IN MODERATING THE INFLUENCE OF PRODUCT QUALITY ON CONSUMER PURCHASE DECISIONS (A STUDY ON CONSUMERS OF LUXCRIME BLUR & COVER TWO WAY CAKE PRODUCTS IN DENPASAR CITY) - Ni Luh Ayu Yuliantari; Putu Yudi Setiawan, I Gusti Ayu Ketut Giantari, I Nyoman Nurcaya (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
Consumer purchase decisions for cosmetic products are influenced by various factors, including product quality and the impact of electronic word of mouth (e-WOM). In today's digital era, e-WOM has become one of the key elements shaping consumer perceptions of a product, especially in the highly competitive beauty industry. This study aims to examine and explain the role of e-WOM in moderating the influence of product quality on consumer purchase decisions. The research was conducted on consumers of Luxcrime Blur & Cover Two Way Cake in Denpasar City, with a sample size of 150 consumers obtained using a non-probability sampling method. Data collection was carried out by distributing questionnaires. The analytical technique employed was Structural Equation Modeling (SEM) with a Partial Least Square (PLS) approach. The results of the analysis indicate that: Product quality has a positive and significant effect on consumer purchase decisions, e-WOM has a positive but not significant effect on consumer purchase decisions, and e-WOM moderates by strengthening the influence of product quality on consumer purchase decisions.